Plasma-Derived microRNAs Are Influenced by Acute and Chronic Exercise in Patients With Heart Failure With Reduced Ejection Fraction - Witvrouwen, Isabel; Gevaert, Andreas B.; Possemiers, Nadine; Ectors, Bert; Stoop, Tibor; Goovaerts, Inge; Boeren, Evi; Hens, Wendy; Beckers, Paul J.; Vorlat, Anne; Heidbuchel, Hein; Van Craenenbroeck, Amaryllis H.; et al. (Frontiers in Physiology, 2021)
Background. Exercise training improves VO2peak in heart failure with reduced ejection fraction (HFrEF), but the effect is highly variable as it is dependent on peripheral adaptations. We evaluated changes in plasma-derived miRNAs by acute and chronic exercise to investigate whether these can mechanistically be involved in the variability of exercise-induced adaptations. Methods. Twenty-five male HFrEF patients (left ventricular ejection fraction <40%, New York Heart Association class ≥II) participated in a 15-week combined strength and aerobic training programme. The effect of training on plasma miRNA levels was compared to 21 male age-matched sedentary HFrEF controls. Additionally, the effect of a single acute exercise bout on plasma miRNA levels was assessed. Levels of 5 miRNAs involved in pathways relevant for exercise adaptation (miR-23a, miR-140, miR-146a, miR-191 and miR-210) were quantified using RT-qPCR and correlated with cardiopulmonary exercise test, echocardiographic, vascular function and muscle strength variables. Results. Expression levels of miR-146a decreased with training compared to controls. Acute exercise resulted in a decrease in miR-191 before, but not after training. Baseline miR-23a predicted change in VO2peak independent of age and left ventricular ejection fraction. Baseline miR-140 was independently correlated with change in load at the respiratory compensation point and change in body mass index, and baseline miR-146a with change in left ventricular mass index. Conclusions. Plasma-derived miRNAs may reflect the underlying mechanisms of exercise-induced adaptation. In HFrEF patients, baseline miR-23a predicted VO2peak response to training. Several miRNAs were influenced by acute or repeated exercise. These findings warrant exploration in larger patient populations and further mechanistic in-vitro studies on their molecular involvement.